Feasibility of conversion of percutaneous cholecystostomy to internal transmural endoscopic ultrasound-guided gallbladder drainage - Chantarojanasiri, Tanyaporn (Saudi J Gastroenterol, 2017)
BACKGROUND/AIM: Percutaneous cholecystostomy [percutaneous transhepatic gallbladder drainage (PTGBD)] is the treatment of choice in surgically unfit patients with acute cholecystitis. However, PTGBD tube removal after symptoms resolution results in 41–46% recurrence. This study aims to demonstrate the feasibility of the conversion of PTGBD to transmural endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) using plastic stents in patients unfit for cholecystectomy. PATIENTS AND METHODS: Patients who underwent internal transmural EUS-GBD as a conversion from PTGBD were reviewed. EUS-GBD was performed after the improvement of cholecystitis due to recurrent cholecystitis and PTGBD intolerance. One or two 7-Fr double pigtail plastic stent insertion with or without temporary endoscopic naso-gallbladder drainage (ENGBD) insertion was performed. RESULTS: Six patients (age 61–88), with three cases of acute cholecystitis after metallic biliary stenting and three cases of calculus cholecystitis, who underwent PTGBD were included. EUS-GBD was performed 10–63 days after PTGBD, using one plastic stent in five cases, two stents in one case, with temporary ENGBD in two cases. The technical success and clinical success were achieved and the PTGBD tubes were subsequently removed in all patients. All ENGBD tubes were removed within 5 days after insertion. Bile leak with peritonitis was demonstrated in one case, which was treated conservatively. No recurrent cholecystitis was seen during 3–26 months of follow-up. CONCLUSION: The conversion of percutaneous cholecystostomy to internal transmural EUS-GBD with plastic stents is feasible for patients unfit for cholecystectomy. However, more studies are still needed to confirm the results.